ANALISA PEMELIHARAAN PREVENTIF PADA ALAT PHOTOTHERAPY DI RUMAH SAKIT BUNDA THAMRIN - Simbolon, Samuel William; Sijabat, Salomo; Abdillah, Khairil (Prodi Teknik Elektromedik Universitas Sari Mutiara Indonesia, 2023)
Phototherapy serves as a therapeutic intervention for newborns diagnosed with hyperbilirubinemia or jaundice. This thesis presents the design and implementation of a phototherapy device utilizing LED technology based on an Arduino platform. The primary objective of this research is to develop a phototherapy instrument equipped with LEDs that effectively reduces bilirubin levels in jaundiced infants. The device is structured around three main subsystems: the input subsystem, the data processing subsystem, and the output subsystem. The input subsystem comprises two key components: the LM35 sensor, which monitors the infant's body temperature, and a push button that facilitates therapy control. The data processing subsystem employs an Arduino Uno microcontroller, which acts as the central processing unit for the entire system. The output subsystem includes three components: a blue LED that serves as the therapeutic light source, a buzzer that functions as an alarm, and a Bluetooth HC-05 module that establishes a connection between the device and an Android smartphone. Testing results indicate that all components operate effectively, with the LM35 sensor achieving an accuracy level of 98.5% in monitoring the infant's temperature. The Bluetooth module operates reliably at a distance of 10 meters. The optimal distance for the device's operation is approximately 20-30 cm to ensure that the intensity of the blue LED reaches or exceeds 30 µW/cm²/nm.